Development of Concept Mapping as Optimizing Apperception of Learning for Social Arithmetic Materials - Fitri Umardiyah; Apriana Nur Handhayani (APPLICATION: Applied science in Learning Research, 2022)
The development of concept mapping as an optimization of the learning apersepsi of social arithmetic materials in grade VIIA MTs Ghozaliyah Jombang aims to develop a valid and practical concept mapping teaching materials by optimizing student perception. This research is a type of research and development (R&D) with addie model, analysis, design, development, implementation and evaluation. Based on the results of the development that has been done, the final product of research and development is the learning media concept mapping using video on social arithmetic material. Based on the assessment by media experts get a score of 90% with a classification very valid or very worth using. Assessments by material experts score 89% with a very valid classification or very worth using. The results of the student response questionnaire scored 77% with a practical classification. Based on these results, it can be concluded that concept mapping learning media packaged in the form of video is worth using.